2000
DOI: 10.1074/jbc.m002282200
|View full text |Cite
|
Sign up to set email alerts
|

Primary Structure, Genomic Organization, and Functional and Electrogenic Characteristics of Human System N 1, a Na+- and H+-coupled Glutamine Transporter

Abstract: We have cloned the human Na ؉ -and H ؉ -coupled amino acid transport system N (hSN1) from HepG2 liver cells and investigated its functional characteristics. Human SN1 protein consists of 504 amino acids and shows high homology to rat SN1 and rat brain glutamine transporter (GlnT). When expressed in mammalian cells, the transport function of human SN1 could be demonstrated with glutamine as the substrate in the presence of LiCl (instead of NaCl) and cysteine. The transport activity was saturable, pH-sensitive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
97
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 40 publications
5
97
1
Order By: Relevance
“…Therefore, conclusions with regard to oxidative metabolism based on alterations in plasma lactate concentrations should be treated with caution. Indeed, the later peak plasma lactate concentration following glutamine ingestion in the present study demonstrates the many factors that may influence plasma lactate concentration (indeed it is possible that glutamine interferes with either the passive or active export of lactate from the muscle, via monocarboxylate transporter 1; Fei et al 2000). Furthermore, the reduction in lactate concentration in hyperoxia observed in previous studies during submaximal exercise is likely due to a reduction in muscle glycogenolysis (Stellingwerff et al 2005;Stellingwerff, LeBlanc, Hollidge, Heigenhauser & Spriet, 2006).…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, conclusions with regard to oxidative metabolism based on alterations in plasma lactate concentrations should be treated with caution. Indeed, the later peak plasma lactate concentration following glutamine ingestion in the present study demonstrates the many factors that may influence plasma lactate concentration (indeed it is possible that glutamine interferes with either the passive or active export of lactate from the muscle, via monocarboxylate transporter 1; Fei et al 2000). Furthermore, the reduction in lactate concentration in hyperoxia observed in previous studies during submaximal exercise is likely due to a reduction in muscle glycogenolysis (Stellingwerff et al 2005;Stellingwerff, LeBlanc, Hollidge, Heigenhauser & Spriet, 2006).…”
Section: Discussionmentioning
confidence: 70%
“…The carrier of these currents has been discussed controversially. Initially, the transporter was thought to be electrogenic (17), but this was refuted by two subsequent studies (14,15). Further analysis of the currents showed that the reversal potential of the substrate-induced currents varies with pH, and as a result a proton conductance was proposed by Chaudhry et al (14).…”
mentioning
confidence: 97%
“…Uptake of glutamine is coupled to the cotransport of 1Na ϩ and the antiport of 1H ϩ and hence is unaffected by changes of the membrane potential (15,16). However, inward currents are observed during transport (14,15,17). The carrier of these currents has been discussed controversially.…”
mentioning
confidence: 99%
“…Cloning of mouse ATB 0,+ . The SuperScript plasmid system (Life Technologies Inc., Rockville, Maryland, USA) was used to establish a unidirectional cDNA library with poly(A) + RNA isolated from mouse colon as described previously (23)(24)(25). The probe for library screening was prepared by RT-PCR using primers specific for mouse ATB 0,+ cDNA reported in the GenBank (accession no.…”
mentioning
confidence: 99%